The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fcvm.2021.602275
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Implantable Electronic Device Infection and New Insights About Correlation Between Pro-inflammatory Markers and Heart Failure: A Systematic Literature Review and Meta-Analysis

Abstract: Introduction: Surgical approaches to treat patients with abnormal pro-inflammatory parameters remain controversial, and the debate on the correlation between hematological parameter alteration in cardiac implantable electronic device (CIED) infection and the increase in mortality continues.Methods: We performed a systematic review using the PubMed, Scopus, and Cochrane Library databases. Twenty-two articles from May 2007 to April 2020 were selected and divided according to the following topics: prevalence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Besides, systematic inflammation is crucial in the development of post‐CA syndrome 31 . Several previous reports have shown that increased RDW level relates to a lot of misregulations including senescence, oxidative stress, systemic inflammation, malnutrition, and impaired kidney function 32,33 . Because of that, we hypothesize that increased RDW can potentially reflect a poor prognosis on CA patients through misregulations like oxidative stress and systemic inflammation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Besides, systematic inflammation is crucial in the development of post‐CA syndrome 31 . Several previous reports have shown that increased RDW level relates to a lot of misregulations including senescence, oxidative stress, systemic inflammation, malnutrition, and impaired kidney function 32,33 . Because of that, we hypothesize that increased RDW can potentially reflect a poor prognosis on CA patients through misregulations like oxidative stress and systemic inflammation.…”
Section: Discussionmentioning
confidence: 85%
“… 31 Several previous reports have shown that increased RDW level relates to a lot of misregulations including senescence, oxidative stress, systemic inflammation, malnutrition, and impaired kidney function. 32 , 33 Because of that, we hypothesize that increased RDW can potentially reflect a poor prognosis on CA patients through misregulations like oxidative stress and systemic inflammation. More basic research is certainly required for a better understanding of the potential mechanisms included.…”
Section: Discussionmentioning
confidence: 99%
“…Infection is a common and frequent complication associated with all types of biomedical materials, despite the infection rate varying greatly among different intended uses of various implantable devices ( Table 2 ) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Orthopedic implants, such as the ankle, hip, knee, elbow, shoulder, and finger joint prosthetics, are made of metals (titanium alloys, stainless steel, cobalt-chromium alloy, etc.)…”
Section: Clinical Features Of Device-associated Infectionsmentioning
confidence: 99%